INTEGRASI PSIKOLOGI,PEDAGOGI, DAN KONSELING SEBAGAI PENDEKATAN INTERDISIPLINER DALAM PENGUATAN PROFESIONALITAS KONSELOR PENDIDIKAN - Ngampuni; Budiyanto; Evi Winingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The professionalism of educational counselors faces complex challenges in the contemporary era, where student issues are not merely psychological but are also critically related to learning dynamics. This article aims to analyze the integration of psychology, pedagogy, and counseling as an interdisciplinary approach to enhancing the professionalism of educational counselors. This approach posits that these three disciplines do not operate in isolation but are mutually complementary; psychology provides the foundation for understanding developmental stages and personality dynamics, pedagogy offers context regarding how students learn and interact within the educational system, while counseling supplies the techniques and professional relationships necessary for intervention. Through a literature review utilizing a conceptual synthesis approach, this article demonstrates that interdisciplinary integration is capable of improving comprehensive assessment skills, designing contextual interventions aligned with learning needs, and strengthening collaboration with other educational stakeholders. In conclusion, the professionalism of educational counselors cannot be viewed solely through the mastery of counseling techniques; it must also encompass pedagogical literacy and depth of psychological analysis. Recommendations are proposed for counselor education institutions to reform their interdisciplinary-based curricula, and for practitioners to continuously develop their collaborative capacity within the school environment